Oracle Streams 11g Data Replication - Deshpande Kirtikumar (American : MC Graw Hill, 2011)
Enable real-time information access and data sharing across your distributed framework using the expert information in this Oracle Press guide. Oracle Streams 11g Data Replication explains how to set up and administer a unified enterprise data sharing infrastructure. Learn how to capture, propagate, and apply database changes, transform data, and handle data conflicts. Monitoring, optimizing, and troubleshooting techniques are also covered in this comprehensive volume.
Keywords: Computer -Programs; Computer Process; Data transformations